P49 Tuberculosis in Birmingham is Seasonal. (19th November 2012) - Koh, GCKW; Hawthorne, G; Kunst, H; Dedicoat, M
Abstract : Background: Birmingham is a large industrial city with migrant populations from Pakistan, India, Somalia and Eritrea. Central Birmingham is highly endemic for tuberculosis (TB) with an annual incidence 80 per 100, 000. TB is therefore a disease of major public health importance in Birmingham. Objectives: We sought to determine the contribution of seasonal variation to TB incidence in Birmingham. Methods: Information was collected prospectively on all adult TB notifications for Birmingham covering the thirty-year period from 1980 to 2009. Unmeasured component models were used to decompose incidence data into seasonal and long term trends. Results: There were 10, 892 cases of tuberculosis notified during the study period from winter 1988/9 to autumn 2009. There was strong evidence for seasonality in tuberculosis notifications with peaks occurring every summer (Figure 1, AICD 10.5). This seasonality was apparent in both pulmonary and extra pulmonary tuberculosis (AICD 12.1 and 11.0, respectively). There was no support for seasonality in UK-born cases (AICD –12.0), but seasonality was apparent in non-UK born cases (AICD 11.8). Discussion and Conclusion: TB notifications peak every summer and may plausible be linked to conditions in the preceding winter. Winter crowding may lead to increased transmission of tuberculosis, which then manifests as active TB in the summer. Alternatively, reduced exposure to sunshine during the winter and decreased vitamin D levels may result in impaired host defence to tuberculosis. The potential link between seasons and vitamin D levels is interesting, because vitamin D supplementation of at-risk populations is a plausible public health intervention.